Una división esquemática de estrategias de aprendizaje relevantes para el patrimonio cultural basadas en juegos digitales - Champion, Erik (Instituto Nacional de Antropología e Historia, 2017)
How can we transmit the values and interpretations of cultural heritage (using virtual reality) in ways that are relatively inexpensive, contextually appropriate, educationally effective, and collaborative? While much excellent research has been undertaken on social presence in virtual environments (Swinth y Blascovich, 2002), research on the design and evaluation of cultural presence (i.e. the perception another culture is portrayed and experienced in a virtual environment) lags behind. Where cultural presence has been explored, it has not been directed towards the experiencing of culturally significant heritage (Riva et al., 2002), and organizations such as UNESCO have not prescribed how to determine if the user experience achieved the goals of the designers and shareholders (Champion, 2015, 2011). One possible solution for digital archaeology is to deploy commercial games that allow themselves to be modded (as in modified). This paper will provide a simple classification of the ways in which game-based examples may help communicate digital archaeology and related content, and argue that there are at least four major areas of research that need to be investigated further.